2023
DOI: 10.1007/s12144-023-04289-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the structural equation modeling between intrinsic-motivation, emotion regulation and AHDH: the mediating role of problem-solving, time-management, and behavioral-inhibition

Abstract: Although Executive Functions has been considered as the main correlation of ADHD few studies have examined the effect of EFs on ADHD symptoms, in the samples with ADHD. This study aimed to examine the structure of EFs on ADHD students in a hypothesized model. After careful screening of ADHD among 1368 university students (with stratified and multistage cluster sampling), out of them, 211 students with ADHD diagnosis were selected purposefully. They received scales on their emotion regulation, motivation, adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Individuals with low boredom proneness and high behavioral inhibition activity demonstrated the highest anxiety levels. This may arise from the tendency of individuals with high behavioral inhibition to emphasize self-control and self-demand, thereby imposing greater pressure on themselves and experiencing difficulties in emotional regulation, ultimately leading to heightened anxiety ( Afshadi et al, 2023 ). In contrast, individuals with moderate boredom-inhibition group displayed the lowest anxiety levels, possibly because moderate boredom fosters a more relaxed mindset, and appropriate behavioral inhibition enables individuals to confront pressure without resorting to avoidance or negative coping mechanisms, thereby facilitating the mitigation of negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with low boredom proneness and high behavioral inhibition activity demonstrated the highest anxiety levels. This may arise from the tendency of individuals with high behavioral inhibition to emphasize self-control and self-demand, thereby imposing greater pressure on themselves and experiencing difficulties in emotional regulation, ultimately leading to heightened anxiety ( Afshadi et al, 2023 ). In contrast, individuals with moderate boredom-inhibition group displayed the lowest anxiety levels, possibly because moderate boredom fosters a more relaxed mindset, and appropriate behavioral inhibition enables individuals to confront pressure without resorting to avoidance or negative coping mechanisms, thereby facilitating the mitigation of negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis of this study was related to emotion regulation. As research on emotion regulation has shown [60,61], it might not be initial emotional experience but emotion regulation that is related to CPS performance [83,84]. Emotion regulation was assessed with six subscales of emotion regulation styles: Positive Reframing, Self-Reflection, Boost of Self-Confidence, Flight Tendency, Resignation, and Aggression.…”
Section: Discussionmentioning
confidence: 99%